Cumulative sum analysis score and phacoemulsification competency learning curve - Gustavo Vedana; Filipe G. Cardoso; Alexandre S. Marcon; Licio E. K. Araújo; Matheus Zanon; Daniella C. Birriel; Guilherme Watte; Albert S. Jun (International Journal of Ophthalmology, 2017)
AIM: To use the cumulative sum analysis score (CUSUM) to construct objectively the learning curve of phacoemulsification competency. METHODS: Three second-year residents and an experienced consultant were monitored for a series of 70 phacoemulsification cases each and had their series analysed by CUSUM regarding posterior capsule rupture (PCR) and best-corrected visual acuity. The acceptable rate for PCR was <5% (lower limit h) and the unacceptable rate was >10% (upper limit h). The acceptable rate for best-corrected visual acuity worse than 20/40 was <10% (lower limit h) and the unacceptable rate was >20% (upper limit h). The area between lower limit h and upper limit h is called the decision interval. RESULTS: There was no statistically significant difference in the mean age, sex or cataract grades between groups. The first trainee achieved PCR CUSUM competency at his 22nd case. His best-corrected visual acuity CUSUM was in the decision interval from his third case and stayed there until the end, never reaching competency. The second trainee achieved PCR CUSUM competency at his 39th case. He could reach best-corrected visual acuity CUSUM competency at his 22nd case. The third trainee achieved PCR CUSUM competency at his 41st case. He reached best-corrected visual acuity CUSUM competency at his 14th case. CONCLUSION: The learning curve of competency in phacoemulsification is constructed by CUSUM and in average took 38 cases for each trainee to achieve it.